فعالية وسائل الصور الملونة في تعليم المفردات في المدرسة الإبتدائية الحكومية 3 بونوروغا - Zulaini, Nabilla Nurbaiti (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
The objectives of this study is to find out the effectiveness of color image media in mufrodat learning at MIN 3 Ponorogo. Researchers used a quantitative approach to the type of experimental research. the researcher used two classes, namely the experimental class of 25 students and the control class of 25 students. While the data collection techniques used are observation, interviews, tests, questionnaires and documentation. The results of the research in this study is vocabulary learning by using color image media effective to increase the value of student learning outcomes on mufrodat. The effective is proven by the results of the N-gain score test, which shows that the average value for the experimental class is 57.9333 or 57.9%, which is quite effective. With a minimum N-gain score of 0% and a maximum of 100%. while the average N gain score for the control class is 49.2079 or 49.2%, including the less effective category. With a minimum Ngain score of 11.11% and a maximum of 100%.